(untitled) - Latham-Koenig, Christina (Oxford, 2012)
A new edition of the best-selling English File, improved throughout with brand new digital components to use inside and outside the classroom. English File Third edition - the best way to get your students talking.
Keywords: Anh ngữ,English language; Dạy và học,Nói tiếng nước ngoài,Study and teaching,Foreign speakers